Paradoxes in the redefinition of the work of the professorate - Contreras Domingo, José (Education Policy Analysis Archives, 1999)
In the present atmosphere of education reform in Spain, autonomy of the faculty and the educational institutions is continually referred to. "Autonomy" as it is currently used in this context poses a paradox: autonomy as obligation. Not just this paradox but others as well are discussed. The present article is organized in four sections. In the first section, the article analyzes a set of factors (from the new organizational arrangments of social services and their relationship with the State to the current patterns of production and consumption) present in the autonomy rethoric. In the second section the author describes the main changes in the school as institution, changes that are affecting academic and professional autonomy. In the third section, the paradoxes surrounding present policies of scholastic autonomy are analyzed. In the fourth, suggestions are made for recovering the political and pedagogical meaning of autonomy.